Are Hallucinations Due to an Imbalance Between Excitatory and Inhibitory Influences on the Brain? - Jardri, Renaud (Schizophr Bull, 2016)
This review from the International Consortium on Hallucinations Research intends to question the pertinence of the excitatory-to-inhibitory (E/I) imbalance hypothesis as a model for hallucinations. A large number of studies suggest that subtle impairments of the E/I balance are involved in neurological and psychiatric conditions, such as schizophrenia. Emerging evidence also points to a role of the E/I balance in maintaining stable perceptual representations, suggesting it may be a plausible model for hallucinations. In support, hallucinations have been linked to inhibitory deficits as shown with impairment of gamma-aminobutyric acid transmission, N-methyl-d-aspartate receptor plasticity, reductions in gamma-frequency oscillations, hyperactivity in sensory cortices, and cognitive inhibition deficits. However, the mechanisms by which E/I dysfunctions at the cellular level might relate to clinical symptoms and cognitive deficits remain unclear. Given recent data advances in the field of clinical neuroscience, it is now possible to conduct a synthesis of available data specifically related to hallucinations. These findings are integrated with the latest computational frameworks of hallucinations, and recommendations for future research are provided.